Modelling Cadmium adsorption by Coconut Shell Charcoal using the Langmuir and Freundlich Isotherm Expressions - and Ashwani Kumar, Mausumi Raychaudhuri, S. Raychaudhuri, Itishree Manjari Brahma (Journal of the Indian Society of Soil Science, 2016)
Cadmium, widely existing heavy metal in wastewater, enters the food chain when the contaminated water is used for irrigation. Cadmium gets accumulated in the soil and plants and causes toxicity and abnormalities. Excess cadmium intake is carcinogenic in humans and animals which is of great concern. Removal of cadmium from aqueous solution using activated carbon and plant biomass is quite effective. An attempt has been made in this study to use charcoal from coconut shell in an indigenous way to remove cadmium from aqueous solution. To understand the efficiency of coconut shell charcoal (CSC) batch test was conducted and both Freundlich and Langmuir adsorption model fitted well with the experimental data. Further, efficiency of the charcoal was increased by modifying its pH and found effective in removing Cd from aqueous solution.